Optimization and formulation of dissolvable microneedle patch loaded with venlafaxine - Kumar, Deepak; Kalra, Naresh (Journal of Neonatal Surgery, 2025)
The objective of this work was to prepare and optimize dissolvable microneedle formulations loaded with venlafaxine. PVA (2.5 - 20 % w/v) along with or without 20% w/v chitosan were used to prepare the microneedles by casting aqueous solution in the molds. The microneedle patches were evaluated for physical appearance, surface pH, weight uniformity, drug content, moisture content and uptake, insertion capability, mechanical strength, in vitro dissolution capability and in vitro release. Among the ten formulations developed F8, F9 and F10 presented sharp needles whereas the ones with lower PVA ratio had blunt needles and were very plastic to be cast as microneedles. The surface pH ranged from 5.33 to 5.63 suggesting skin compatibility. Venlafaxine loaded microneedle patch was prepare using 5.0%w/v PVA and 20% chitosan. The drug content in the microneedle patch was 97.18%. venlafaxine released in a biphasic manner from the microneedles with an initial burst release within 3 hours releasing about 50% of drug. The burst release could be due to the dissolved microneedle tips in the dermis. After the initial rapid release, the release was found to be prolonged for more than 24h. This biphasic release proﬁle would be able to effectively manage both acute and chronic pain conditions. The results led us to conclude that microneedle patches could be easily prepared using simple casting method and also present effective loading of venlafaxine for managing acute and chronic pain with single application.